Shipbuilding during World War II - Waldmann Júnior, Ludolf (2020)
Changes in shipbuilding in the mid-nineteenth century decisively affected the ability of non-industrialized countries to manufacture modern ships. Given this situation, countries that were not industrialized at that moment, like Brazil, have had to rely on imports to supply their navies with modern vessels. In order to escape from foreign dependence, Brazil, sought to revive its shipbuilding from the 1930s, in an internal environment conducive to industrialization and the environment that had the potential for external support for this endeavor. This article seeks to understand shipbuilding in Brazil during the Second World War from the perspectives of national and international politics of the period, seeking to understand how these junctures influenced the decision of the Brazilian government to build ships in the country.